Export Market Risk and the Role of Public Credit Guarantees - Erdal Yalcin; Inga Heiland (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper we analyze the impact of public export credit guarantees on firms' exports. Earlier studies show that export credit guarantees stimulate exports, employment, and value added. Furthermore, there is evidence at the aggregate level that financial market imperfections are key to understanding the beneficial effects of this policy instrument. We use monthly firm-level survey data combined with official transaction-level data on covered exports of German firms to analyze in detail the hypothesis that the positive effects are due to mitigated financial constraints. Considering exporter and importer characteristics, as well as transaction-specific characteristics, we shed light on the particular sources of financing constraints that can be alleviated by the policy instrument. We find that positive effects are stronger at times when refinancing conditions for the private sector are tight. Furthermore, our results indicate that small firms and firms with little liquid means benefit more, and that the public guarantees matter especially for contracts involving large values at risk. Our analysis contributes to a better understanding of the interplay between export credit guarantees and financial market imperfections, which is crucial for an efficient policy design.
Keywords: F12; F36; G28; 330